Improvised Multipath Cooperative Routing Protocols in WSN’s Reduced Energy Savings–An Overview of the Research Work - Hanumanthappa S. N.,; Girish V. Attimarad, (Journal of Electronic Design Engineering, 2020)
In this paper, an overview of the conceptual development of the improvised multipath cooperative routing protocols in WSN’s using CBR, MPCR, and DSCR with reduced energy savings is being presented in a nutshell. The article gives in-depth info about the research work that is being taken up by the research scholar along with the necessary objectives and the outcomes that are going to be initiated at the start of his Ph.D. research work.